Spektakl w teatrze marionetek. O wierszu Stanisława Barańczaka Bist Du bei mir raz jeszcze - Dembińska-Pawelec, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
This essay presents an interpretation of Stanisław Barańczak’s Bist du bei mir – a poem that has often been the subject of literary studies. The author refers to the poem’s motto – a fragment of an aria by Gottfried Heinrich Stölzel from Clavierbüchlein für Anna Magdalena Bach, often falsely attributed to Johann Sebastian Bach. She also points at the context of mystical poetry: Adam Mickiewicz’s epigrams from Zdania i uwagi z dzieł Jakuba Bema, Anioła Ślązaka (Angelus Silesius) i Sę-Martena [Sentences and remarks. From the works of Jacob Böhme, Angelus Silesius, and St. Martin] and G. Herbert’s poems translated by Barańczak. In the author’s reading, the poet, in an ironic gesture of reference, strips the reader of literary delusions, discovering deeply tragic dimensions of life and, possibly, also of personal experience of suffering.